Ancestor Christology Re-assessing Bénézet Bujo's contribution to African theology - Caldeira, Cleusa; Okpaleke, Ikenna Paschal (2022)
As tentativas de desenvolver uma cristologia a partir de uma perspectiva exclusivamente africana podem ser consideradas uma das expressões contextuais do empreendimento teológico cristão. É claro que, no contexto do Cristianismo mundial, toda teologia é contextual. Este artigo, explora criticamente as ideias cristológicas de um dos principais teólogos africanos, Bénézet Bujo, situa as muitas reflexões sobre Cristo no contexto africano. O artigo argumenta consistentemente a favor da necessidade da cristologia africana e de uma compreensão aprofundada do argumento de Bujo, para tornar a pessoa de Cristo inteligível na África, empregando a categoria tradicional africana de ancestral. O ancestral como paradigma cristológico permanece controverso, pois levanta muitas questões quanto à sua adequação na compreensão de Cristo para os cristãos africanos. No entanto, a avaliação do paradigma deve ir além da busca de uma interpretação lógica que o vincule às formulações cristológicas predominantes do Ocidente, para buscar o significado da revelação dentro da cosmovisão africana. Este artigo, portanto, avalia as percepções de Bujo e destaca as deficiências de seus argumentos, ao mesmo tempo, chama mais atenção para seu alcance ético e catequético.
Attempts at developing a Christology from a uniquely African perspective could be considered as one of the contextual expressions of Christian theological enterprise. Of course, it is clear that within the context of world Christianity, every theology is contextual. This article, which critically explores the Christological ideas of one of the foremost African theologians, Bénézet Bujo, locates the many reflections about Christ within the African context. The article consistently argues for the necessity of African Christology and for a deepened understanding of Bujo's argument in making the person of Christ intelligible within Africa by deploying the traditional African category of ancestorship in this regard. Ancestorship as a Christological paradigm remains contentious as it raises a lot of questions as to its appropriateness in the understanding of Christ for African Christians. Yet, the assessment of the paradigm must go beyond seeking a logical interpretation that ties it to the predominant Christological formulations of the West to seek the meaning of revelation within the African worldview. This article, therefore, appraises the insights of Bujo and highlights the deficiencies of his arguments, while calling for more attention to its ethical and catechetical import.
Keywords: Bénézet Bujo; Cristo Proto-Ancestral; Cristologia; Inculturação; Teologia africana